(AS)Sexualidades: processo de subjetivação e resistência - Santos, Valéria Konc dos (2016)
The term asexuality is understood in this work as a sexuality array characterized by the absence of sexual attraction or/and sexual activity. Asexuality has become of popular interest over the last years as the mainstream media has given some attention to the subject. Seen as a “novelty” in sexual multiplicities, it still needs further research. This dissertation embraces a theoretical investigation, approaching the locus of communities in virtual space and support forums. It addresses the problem of conceptualization and apprehension of asexuality in a context which many of its features are tangled in essentialist discourses (that define it as a fourth sexual orientation), political and identity discourses (especially when it becomes a movement fighting for recognition — observed in the major asexual communities), or in subject's singular processes. On the other hand, it also can be problematized through the queer approach directed at deconstructing and subverting heteronormative sexuality, as asexuality phenomena also strengthens the struggle and creation of that “new” that disturbs the status quo. People who think of themselves as asexual are beyond the limits of normative sexuality. They affirm that their condition is not a result of trauma, sexual repression, hormonal problems, religious choice, or explained by any other regulatory discourse. Thus, the discussion proposed here indicates that asexual people show rhizomatic and polymorphic sexuality. Although asexuality is encompassed in historical and social conditions that still nourish conservative and colonial thoughts, the conclusion of this work suggests that sexuality may be viewed as a line of flight and, therefore, it entails a micro-political force that struggles to prevent its own suppression as well as its weakening